ANJANA: A REVIEW ARTICLE - Dwivedi Pramod Chandra; Pande Pulsi; Kawthekar Prachi; Vyas M.K.; Singh Dinesh Gaur (International Journal of Applied Ayurved Research, 2016)
Kriyakalpa is the basis of the ophthalmic disorders, as Panchakarma is the basis of Kayachikitsa. When we refer to our classics for the therapeutic measures adopted in the management of eye diseases, we find that the management includes many of the topical treatments along with systemic ones. The reason might be that the drugs administered systematically may not cross the blood aqueous, blood-vitreous and blood-retinal barriers. Now the topical measures came into play and these are called as ‘Kriya Kalpa’. No specific definition of Kriyakalpa has been given by the ancient scholars except the commentator Dalhana who opines that Kriyakalpa includes various preparations like Tarpana, Putapaka, Seka, Ashchyotana, Anjana etc. for the treatment of eye diseases, as a local measure. The process in which herbo mineral preparation (Gutika, Rasakriya & Churna) mix with water and apply on the eyelids with the help of Shalaka is called Anjana Karma. An Ayurvedic review & probable mode of action of Anjana Karma discussed in present article.